Noradrenaline Increases mEPSC Frequency in Pyramidal Cells in Layer II of Rat Barrel Cortex via Calcium Release From Presynaptic Stores - Choy, Julian M. C.; Agahari, Fransiscus A.; Li, Li; Stricker, Christian (Frontiers in Cellular Neuroscience, 2018)
Somatosensory cortex is innervated by afferents originating from the locus coeruleus which typically release noradrenaline. We tested if activation of presynaptic α1-adrenoceptors (AR) coupled to a Gq-mediated signalling cascade resulted in calcium (Ca2+) release from stores and thereby increased spontaneous transmitter release in rat barrel cortex. Adding 1 - 100 µM noradrenaline (NA) or 5 µM cirazoline (CO), a α1-AR specific agonist, to the standard artificial cerebrospinal fluid increased the frequency of miniature excitatory postsynaptic currents (mEPSC) by 64 ± 7% in 51% of pyramidal cells in layer II (responders) with no effect on the amplitude. In 42 responders, the mEPSC frequency during control was significantly smaller (39 ± 2 vs. 53 ± 4 Hz) and upon NA exposure, the input resistance (Rin) decreased (9 ± 7%) compared to non-responders. Experiments using CO and the antagonist prazosin revealed that NA acted via binding to α1-ARs, which was further corroborated by simultaneously blocking β- and α2-ARs with propranolol and yohimbine, which did not prevent the increase in mEPSC frequency. To verify elements in the signalling cascade, both the phospholipase C inhibitor edelfosine and the membrane permeable IP3 receptor blocker 2-APB averted the increase in mEPSC frequency. Likewise, emptying Ca2+ stores with cyclopiazonic acid or the chelation of intracellular Ca2+ with BAPTA-AM prevented the frequency increase, suggesting that the frequency increase was caused by presynaptic store release. When group I metabotropic glutamate receptors were activated with DHPG, co-application of NA occluded a further frequency increase suggesting that the two receptor activations may not signal independently of each other. The increased mEPSC frequency in a subset of pyramidal cells results in enhanced synaptic noise, which, together with the reduction in Rin, will affect computation in the network.